Strategic Foresight and -Analysis : Merging foresight and intelligence through probabilistic futures - Räihä, Linda (My University, 2025)
The thesis explores the potential integration of strategic foresight and strategic intelligence analysis through the perspective of probabilistic futures. By combining practically elements from both domains, the resulting information aims to provide enhanced value and accuracy, serving as a more effective tool to support strategic decision-making process in foresight. The study incorporates risk management through numeric evaluation through future events, introducing the static rigor to the assessment. This adjustment allows the transformation of qualitative data into the quantitative format, thereby accelerating the process through data process of prototype formulas. Combination of Analysis of Competing Hypotheses and Delphi method are a basis of methodological elements of this study. These structural frameworks of intelligence and foresight are the building blocks of the thesis alongside human cognition included in them. Strategic design structure gathers around design thinking and lean philosophy. Resulting tool Foresight & Analysis (F&A) is a beneficial, yet raw tool for organizational strategic aid providing most likely scenarios and future events scenarios includes. The combination of different future study and intelligence methods and approaches crystalizes into developing a fast and easy to use study method and potential development of a tool into a test prototype. Potential development of the tool with artificial intelligence and good human user interference, probabilistic are possible to utilize in rapid pace in strategic decisions. The tool accelerates the data collection process, which prevents the information to outdate in the changing informative society we live in. Monitoring of future events gives more profound insight to scenarios, which aids operative actions. The thesis recombines strategic foresight with a new tool that transforms data into actionable insights, empowering organizations to outpace uncertainty and shape the future.
Keywords: intelligence, foresight, strategy, analysis, decision-making, risk management